Stigma towards women requesting abortion and association with health facility staff facilitation and obstruction of abortion care in South Africa - Jim, Abongile; Magwentshu, Makgoale; Menzel, Jamie; Küng, Stephanie Andrea; August, Sa-Asa; van Rooyen, Justine; Chingwende, Rumbidzayi; Pearson, Erin (Frontiers in Global Women's Health, 2023)
Background Abortion stigma has been shown to influence provider attitudes around abortion and may decrease provider willingness to participate in abortion care, or lead some to obstruct care. However, this link remains understudied. Methods The present study uses baseline data collected through a cluster-randomized controlled trial in 16 public sector health facilities in South Africa in 2020. A total of 279 clinical and non-clinical health facility workers were surveyed. Primary outcome measures included: 1) willingness to facilitate abortion care in eight hypothetical scenarios, 2) facilitation of abortion care in the last 30 days, and 3) obstruction of abortion care in the last 30 days. Logistic regression models were used to assess the association between level of stigma as measured through the Stigmatizing Attitudes, Beliefs and Actions Scale (SABAS) and the primary outcomes. Results Overall, 50% of respondents in the sample were willing to facilitate abortion care in each of the eight scenarios, with differences in willingness based on the abortion client's age and personal situation in each scenario. Over 90% reported facilitating abortion care in the last 30 days, but 31% also reported having obstructed abortion care in the last 30 days. Stigma was significantly associated with willingness to facilitate abortion care and actual obstruction of abortion care in the last 30 days. Controlling for covariates, odds of willingness to facilitate abortion care in every scenario decreased with every one-point increase in SABAS score (reflecting more stigmatizing attitudes), and odds of obstructing abortion care increased with every one-point increase in SABAS score. Conclusions Lower abortion stigma on the part of health facility workers was associated with willingness to facilitate abortion access but not actual facilitation of abortion services. Higher abortion stigma was associated with actual obstruction of an abortion service in the last 30 days. Interventions to reduce stigma towards women seeking abortion, and particularly negative stereotyping, among all health facility staff is key to ensuring equitable and non-discriminatory access to abortion. Trial registration Retrospectively registered on clinicaltrials.gov (ID: NCT04290832) on February 27, 2020. Plain english summary The link between stigma against women seeking abortion and decisions around whether to provide, abstain, or obstruct abortion care remains understudied. This paper assesses how stigmatizing beliefs and attitudes towards women seeking abortion in South Africa affects willingness to facilitate abortion care and actual facilitation or obstruction of abortion care in practice. A total of 279 clinical and non-clinical health facility workers were surveyed between February and March 2020. Overall, half of respondents in the sample were willing to facilitate abortion care in each of the eight scenarios, with important differences in willingness by scenario. Almost all respondents reported facilitating an abortion procedure in the last 30 days, but one in three also reported having obstructed abortion care in the last 30 days. More stigmatizing attitudes corresponded to decreased willingness to provide abortion care and increased odds of obstructing abortion care. Results show that stigmatizing attitudes, beliefs, and actions toward women who seek abortion shape how clinical and non-clinical staff in South Africa feel about their participation in abortion services and whether they obstruct this care. Facility staff hold great power in determining whose abortions are facilitated and whose are obstructed, resulting in stigma and discrimination being openly perpetuated. Continuous work to reduce stigma towards women seeking abortion among all health workers is key to ensuring equitable and non-discriminatory access to abortion for all.